Irrigating alfalfa with limited water supplies - Hanson, Blaine, author; Orloff, Steve, author; Bali, Khaled, author; Sanden, Blake, author; Putnam, Dan, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
The evapotranspiration (ET) of fully-irrigated alfalfa ranges from 31.9 inches in northern California to 65.2 inches in the low desert areas of southern California. During low water years, however, ET may be reduced by limited amounts of applied water. Strategies for coping with limited water supplies include reducing the irrigated acreage (Strategy 1), fully-irrigating the earlier harvest periods until the water supply is used up and then no irrigation thereafter (Strategy 2), and deficit irrigate the field for the entire season by reducing the water applications between harvests (Strategy 3). An evaluation showed slight differences in returns to land and management between the first two strategies. The third strategy could not be adequately evaluated because of the lack of both cost data and yield-ET relationships under deficit irrigation.
USCID water management conference
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.